Factors associated with shoulder pain and disability among Nepalese farmers - Bimali, Inosha; Vongsirinavarat , Mantana; Krityakiarana , Warin; Mathiyakom , Witaya (International Journal of Occupational Safety and Health, 2025)
Introduction: Shoulder pain (SP) is a common concern impacting the quality of life (QOL) and productivity among Nepalese farmers. However, the factors contributing to SP are not fully understood. This study aimed to identify the bio-psychosocial factors influencing SP and disability in Nepalese farmers. Methods: 122 full-time farmers seeking treatment for SP participated in this cross-sectional study. The Nepalese version of the Shoulder Pain and Disability Questionnaire (SPADI-NP), the 11-item Tampa Scale of Kinesiophobia (TSK-11-NP), and the Pain Catastrophizing Scale (PCS-NP) were used for data collection. Univariate and multivariate linear regressions were used to determine the contributing factors of SP and disability. Results: TSK-11-NP, PCS-NP, age, gender, and education were significantly associated with the SPADI-NP, with TSK-11-NP (R2=0.42) and PCS-NP (R2=0.40) demonstrating the highest association. The first model with a constant and TSK-11-NP explained 42% of the variance in SPADI-NP. Adding age, gender, and education sequentially, the model improved the ability to explain the variance in SPADI-NP to 46%, 48%, and 50%, respectively. The results indicated that psychological factors were the strongest factor associated with SP and disability in Nepalese farmers. Conclusions: Heightened kinesiophobia, pain catastrophization, advancing age, female gender, and low level of education significantly contributed to SP and disability in Nepalese farmers. A comprehensive approach addressing these bio-psychosocial factors would be necessary for managing SP and disability and possibly improving the QOL of the local farmers in the region.